Answer:
Explanation:
The formula for the nth term of a geometric sequence is expressed as follows
Tn = ar^(n - 1)
Where
Tn represents the value of the nth term of the sequence
a represents the first term of the sequence.
n represents the number of terms.
From the information given,
r = 1/3
T3 = - 81
n = 3
Therefore,
- 81 = a× 1/3^(3 - 1)
-81 = a × (1/3)^2
-81 = a/9
a = -81 × 9 = - 729
The exponential equation for this sequence is written as
Tn = - 729 * (1/3)^(n-1)
Therefore, to find the second term,T2, n = 2. It becomes
T2 = - 729 * (1/3)^(2-1)
T2 = - 729 * (1/3)^1
T2 = - 729 * (1/3)
T2 = - 243